Soft Power, Crisis of Existence and the Tribal People of Kerala:A Study of Mother Forest, the Unfinished Story of C. K. Janu - Das, Shruti (Literary Studies, 2022)
Joseph Nye coined the term “soft power” which he says means “getting others to want the outcomes that you want.” The world’s largest democracy India is also the home of millions of impoverished people including many indigenous tribes that are impediments to the desired rapid economic and political growth of India. Mother Forest: The Unfinished Story of C. K. Janu, written by Janu Bhaskaran and translated from the original Malayalam into English by N. Ravi Shanker, narrates the story of the struggle of the Adiyas, a tribal people of Kerala, whose identity and livelihood is threatened when they are dispossessed of their ancient land in the forest. The tribe is led by Janu, a girl from their community, whose struggles against the soft power of the State inform the crisis of existence of these tribal people. This paper will attempt to study the crisis of existence of the tribal people in the narrative of Mother Forest using Nye’s theory of “soft power”. This paper will attempt to expose the authoritarianism of State policies vis a vis the helplessness of the indigenous people in the face of displacement from their original habitat as described in Mother Forest.